2005
DOI: 10.1038/nm1284
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of PI3Kγ suppresses joint inflammation and damage in mouse models of rheumatoid arthritis

Abstract: Phosphoinositide 3-kinases (PI3K) have long been considered promising drug targets for the treatment of inflammatory and autoimmune disorders as well as cancer and cardiovascular diseases. But the lack of specificity, isoform selectivity and poor biopharmaceutical profile of PI3K inhibitors have so far hampered rigorous disease-relevant target validation. Here we describe the identification and development of specific, selective and orally active small-molecule inhibitors of PI3Kgamma (encoded by Pik3cg). We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
662
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 716 publications
(692 citation statements)
references
References 39 publications
26
662
3
1
Order By: Relevance
“…The results confirmed that 9AA treatment results in downregulation of p110g levels. In addition, whereas p110g expression Small molecule targeting AKT/mTOR, PI3K, NF-jB and p53 pathways C Guo et al was previously shown to be limited to cells of hematological origin (Camps et al, 2005;Rommel et al, 2007), we found that p110g is expressed in tumor cell lines of various origins, including RCC, fibrosarcoma (HT1080), colon carcinoma (HCT116). We tested different 9AA doses and lengths of treatment and observed downregulation of p110g expression as early as 4-8 h after treatment with at least 5 mM 9AA (Figure 1 and data not shown).…”
Section: P110g Expression Is Decreased In Tumor Cells Treated With 9aamentioning
confidence: 56%
See 1 more Smart Citation
“…The results confirmed that 9AA treatment results in downregulation of p110g levels. In addition, whereas p110g expression Small molecule targeting AKT/mTOR, PI3K, NF-jB and p53 pathways C Guo et al was previously shown to be limited to cells of hematological origin (Camps et al, 2005;Rommel et al, 2007), we found that p110g is expressed in tumor cell lines of various origins, including RCC, fibrosarcoma (HT1080), colon carcinoma (HCT116). We tested different 9AA doses and lengths of treatment and observed downregulation of p110g expression as early as 4-8 h after treatment with at least 5 mM 9AA (Figure 1 and data not shown).…”
Section: P110g Expression Is Decreased In Tumor Cells Treated With 9aamentioning
confidence: 56%
“…Under normal conditions p110g expression is largely restricted to the hematopoietic system, although it can also be detected in endothelium, heart and brain (Camps et al, 2005). Genetic inactivation of p110g allows normal development to adulthood, but causes defects in the immune system (Ru¨ckle et al, 2006).…”
Section: Small Molecule Targeting Akt/mtor Pi3k Nf-jb and P53 Pathwmentioning
confidence: 99%
“…Studies with these inhibitors support the following conclusions: (1) p110a is the primary insulin responsive PI3K in adipocytes and myotubes and is the major PI3K associated with insulin receptor substrate-1 (IRS-1) , (2) p110b contributes to the pathogenesis of arterial thrombosis (Jackson et al, 2005), (3) p110g mediates inflammation in a model of rheumatoid arthritis (Camps et al, 2005) and (4) p110d is an essential component of neutrophil directional movement (Sadhu et al, 2003) and plays a role in cell proliferation of acute myeloid leukemia (Sujobert et al, 2005).…”
Section: Introductionmentioning
confidence: 88%
“…Therefore, PI3K has become the subject of impressive pharmacological efforts as a target to treat inflammatory disease 5,99 . PI3K inhibitors (for example, AS605240) have shown therapeutic effects in mouse models of rheumatoid arthritis 100 and systemic lupus erythematosus 101 , in which the compounds attenuated the migration of neutrophils and lymphocytes, respectively, into inflamed tissue.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%